Polymorphisms in SHISA3 and RFC3 genes and their association with feed conversion ratio in Hu sheep - Lin, Changchun; Wang, Weimin; Zhang, Deyin; Huang, Kai; Li, Xiaolong; Zhang, Yukun; Zhao, Yuan; Wang, Jianghui; Zhou, Bubo; Cheng, Jiangbo; Xu, Dan; Li, Wenxin; et al. (Frontiers in Veterinary Science, 2023)
In animal husbandry, feed efficiency is a crucial economic trait. In this study, the general linear model was used to perform association analysis for various genotypes and feed conversion ratio (FCR)-related traits. SNPs in the NC_040257.1:c.625 T > C and NC_040261.1:g.9905 T > C were analyzed whether they were associated to feed efficiency parameters in Hu sheep (body weight, feed intake, average daily growth, and feed conversion ratio). NC_040257.1:c.625 T > C was shown to be significantly associated with body weight at 80, 100, and 120 days as well as feed conversion ratio (P < 0.05), whereas NC_040261.1:g.9905 T > C was found to be significantly associated with average daily weight gain from 80-140 days (ADG80-140) and FCR (P < 0.05). In Hu sheep, the CC genotypes of SHISA3 and RFC3 were the most common genotypes related to feed efficiency traits. Furthermore, the feed conversion ratio of the combined genotypes TTSHISA3-CCRFC3, TTSHISA3-CTRFC3, TTSHISA3-TTRFC3, CTSHISA3-CCRFC3 and CTSHISA3-CTRFC3 was significantly better than the FCR of CCSHISA3-TTRFC3. Reverse transcription-quantitative PCR (RT-qPCR) was used to detect the expression of SHISA3 and RFC3 mRNA levels in 10 tissues from 6 sheep. The results showed that the expression levels of SHISA3 were lower in the lung than in spleen, kidney, muscle and lymph (P < 0.05), and RFC3 was the lung had a highly significant higher expression level than the heart, liver, spleen, and muscle (P < 0.01). In conclusion, SHISA3 and RFC3 polymorphisms can be used as genetic markers for improving feed conversion efficiency in Hu sheep.